Non-alcoholic fatty liver disease in asymptomatic young adults: association with HOMA, metabolic syndrome, and atherogenic risk - Chávez-Pagola , Jorge Teodoro; Hernández-Zavala , Araceli; Valenzuela-Limon, Olga; Sánchez-Gutiérrez , Manuel; Izquierdo-Vega, Jeannett Alejandra (International Journal of Medicine, 2022)
Objective: Non-alcoholic fatty liver disease (NAFLD) represents the most common liver disease worldwide. The Latin American population has the highest obesity rates in the world. The aim was to research the factors associated with NAFLD in young adults. Methods: A cross-sectional study was performed on 171 participants with an average age of 21 years who underwent a physical and laboratory examination, anthropometric evaluation, and abdominal ultrasound. Results: Subjects with NAFLD were significantly overweight, with dyslipidemia, and with atherogenic risk. They had the presence of metabolic syndrome compared to those without NAFLD. Bivariate logistic regression showed that body mass index, atherogenic risk, Homeostatic Model Assessment (HOMA) value, and metabolic syndrome were associated with NAFLD development. Conclusions: The variables of HOMA, metabolic syndrome, and atherogenic risk were most associated as risk predictors of this pathology in young adults.